Resistencia a la humedad y al secado de un suelo estabilizado con cal modificado con escoria de acero y reforzado con fibras (2021)
The investigation dealt with the stabilization of expansive soil with combinations of lime, steel slag and reinforced with two types of fibres, copper filaments and polypropylene fibres. The investigation began with the characterization of the soil for its geotechnical properties. The initial consumption of lime required for the modification of the soil properties was determined from the Eades and Grim pH test. Cylindrical specimens of soil with dimensions 38 mm x 76 mm were cast using this lime content as a stabilizer along with varying quantities of steel slag for determination of optimum steel slag content. The pure lime stabilized soil as well as lime-steel slag modified soil specimens were reinforced with different proportions of copper filaments for determination of optimum fibre content. One dosage of polypropylene fibres was also adopted as reinforcement in specimen preparation. The optimal combinations identified were then subjected to a maximum of three cycles of wetting and drying followed by determination of unconfined compression strength (UCS). The expansive soil required a minimum of 3% lime for its modification. The optimum dosage of steel slag was identified as 5% and optimum copper filament content as 1%. Polypropylene content of 0.3% was also adopted as one combination. The results of the investigation revealed that lime stabilized fibre-reinforced soil with copper filaments was the most durable combination followed by polypropylene fibres. The introduction of steel slag in the mix could not generate enough beneficial durability to the soil after three cycles of wetting and drying.